ABOUT INFLUENCE OF THE INDEX OF SOCIAL WELLBEING OF SCHOOLS ON EDUCATIONAL RESULTS - Melnik, Valentin; Vanin, Aleksandr (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Providing high quality education is one of the important priorities of the State educational policy in the Russian Federation. The main problem of inequality in education is currently associated with the breakdown of schools on educational outcomes. Along with the successful and wealthy schools elevated (gymnasium and lyceums) a whole group of schools with persistently low results students. In these schools concentrate children from disadvantaged families and families with low social status, children with deviant behavior. Accounting of contextual factors at assessment of educational results of pupils is an important task. Especially relevant it looks concerning group of schools which are in adverse social conditions. For identification of such schools it is offered to use an integrated indicator - the index of social wellbeing of school (ISWS). The purpose of work to investigate communication of the index of social wellbeing of schools with educational results. The described technique was approved in the Pskov region. Results of the analysis allowed to classify schools by four groups: high educational results – high ISWS; low educational results – low ISWS; low educational results – high ISWS; high educational results – low ISWS. According to the analysis there is possible a differentiated policy for different groups of schools.